Quantification of lumbar vertebral fat deposition: Correlation with menopausal status, non-alcoholic fatty liver disease and subcutaneous adipose tissue - Zheng, Chu-Shan; Wen, Hui-Quan; Lin, Wu-Sheng; Luo, Xiao-Wen; Shen, Li-Shan; Zhou, Xiang; Zou, Feng-Yun; Li, Qing-Ling; Hu, Hui-Jun; Guo, Ruo-Mi (Frontiers in Endocrinology, 2023)
Purpose To assess abdominal fat deposition and lumbar vertebra with iterative decomposition of water and fat with echo asymmetry and least-squares estimation (IDEAL-IQ) and investigate their correlation with menopausal status. Materials and Methods Two hundred forty women who underwent routine abdominal MRI and IDEAL-IQ between January 2016 and April 2021 were divided into two cohorts (first cohort: 120 pre- or postmenopausal women with severe fatty livers or without fatty livers; second cohort: 120 pre- or postmenopausal women who were obese or normal weight). The fat fraction (FF) values of the liver (FFliver) and lumbar vertebra (FFlumbar) in the first group and the FF values of subcutaneous adipose tissue (SAT) (FFSAT) and FFlumbar in the second group were measured and compared using IDEAL-IQ. Results Two hundred forty women were evaluated. FFlumbar was significantly higher in both pre- and postmenopausal women with severe fatty liver than in patients without fatty livers (premenopausal women: p < 0.001, postmenopausal women: p < 0.001). No significant difference in the FFlumbar was observed between obese patients and normal-weight patients among pre- and postmenopausal women (premenopausal women: p = 0.113, postmenopausal women: p = 0.092). Significantly greater lumbar fat deposition was observed in postmenopausal women than in premenopausal women with or without fatty liver and obesity (p < 0.001 for each group). A high correlation was detected between FFliver and FFlumbar in women with severe fatty liver (premenopausal women: r=0.76, p<0.01; postmenopausal women: r=0.82, p<0.01). Conclusion Fat deposition in the vertebral marrow was significantly associated with liver fat deposition in postmenopausal women.